Superiority of mature differentiated cultured human corneal endothelial cell injection therapy for corneal endothelial failure - Ueno, Morio; Toda, Munetoyo; Numa, Kohsaku; Tanaka, Hiroshi; Imai, Kojiro; Bush, John; Teramukai, Satoshi; Okumura, Naoko; Koizumi, Noriko; Yamamoto, Akihisa; Tanaka, Motomu; Sotozono, Chie; et al. (American journal of ophthalmology, 2022)
PURPOSE - To investigate the safety and efficacy of cultured human corneal endothelial cell (hCEC) injection therapy with mature differentiated (mature) cell subpopulations (SPs) for corneal endothelial failure (CEF). - DESIGN - Comparative, interventional case series. - METHODS - This study involved 18 eyes with CEF that underwent cultured hCEC injection therapy, categorized into 2 groups: (1) 11 eyes administered a relatively lower proportion (0.1 to 76.3%) of mature cell SPs (group 1 [Gr1]), and (2) 7 eyes administered a relatively higher proportion (>90%) of mature cell SPs (group 2 [Gr2]). From 1 week to 3 years postoperation, corneal endothelial cell (CEC) density (CECD), central corneal thickness (CCT), and best-corrected visual acuity (BCVA) were recorded, and the CEC parameter's “spring constant” was calculated. The proportion of mature SPs was evaluated by fluorescence-activated cell sorting analysis based on cell-surface markers. - RESULTS - At 3 years postoperation, corneal restoration with improved BCVA was attained in 10 of the 11 Gr1 eyes and all Gr2 eyes, the median CECD in Gr2 (3083 cells/mm2; range, 2182-4417 cells/mm2) was higher than that in Gr1 (1349 cells/mm2; range, 746-2104 cells/mm2) (P < .001), and the spring constant verified the superiority of the mature cultured hCECs. From 24 weeks through 3 years postoperation, the median percentage of CECD decrease was 3.2% in Gr2 and 23.6% in Gr1 (P < .005). CCT recovery was prompt and constant in Gr2, while diverse in Gr1. No adverse events were observed. - CONCLUSION - Our findings showed that mature cell SPs for hCEC injection therapy provide rapid recovery of CCT, better CECD, and low CECD attrition over 3 years postsurgery.
Available online 14 November 2021
Gesehen am 19.08.2022